2017
DOI: 10.1039/c7py01659j
|View full text |Cite
|
Sign up to set email alerts
|

Post-polymerization modification of styrene–maleic anhydride copolymer brushes

Abstract: Amine-anhydride reactions on polymer brushes provide a modular post-modification strategy to functional surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Another way of manufacturing TRPBCs involves non-controllable surface-initiated polymerization using multifunctional peroxide initiators or azo initiators [ 88 , 89 , 90 , 91 ]. Sometimes, the application of the coatings does not require high monodispersity of the brush, and non-controllable polymerization may be employed as well.…”
Section: Fabrication Of Trpbc Coatingsmentioning
confidence: 99%
“…Another way of manufacturing TRPBCs involves non-controllable surface-initiated polymerization using multifunctional peroxide initiators or azo initiators [ 88 , 89 , 90 , 91 ]. Sometimes, the application of the coatings does not require high monodispersity of the brush, and non-controllable polymerization may be employed as well.…”
Section: Fabrication Of Trpbc Coatingsmentioning
confidence: 99%
“…Low conversion for the thiol-Michael reaction is likely due to the inefficient penetration of the bulky, large molecular mass and non-polar nature of the PFDA molecule into the BBA-modified brush, hindering access to the thiol throughout the brush. 42 Similarly, Klok and coworkers have shown that the size and polarity of the molecules employed in PPM of brush surfaces play important roles in determining conversion and compositional distribution of the postmodified brush. 43,44 Next, we explored one-pot PPM reactions to produce multifunctional homopolymer brush surfaces.…”
Section: Post-polymerization Modification (Ppm) Of Paht Brush Surfaces and Sequential Thiol-michael Reactionsmentioning
confidence: 98%
“… 106 An alternative strategy based on thiol–ene coupling was to thiolate polymer brushes via the reaction of cystamine with poly(maleic anhydride- co -styrene) brushes, followed by reaction with various acrylates. 107 This approach has the benefit of enabling access to a broad range of acrylate building blocks for functionalisation, although possible disulfide bond formation may affect the brush swelling and physico-chemistry.…”
Section: Side Chain Functionalisation Strategiesmentioning
confidence: 99%